The Effect of Contextual Teaching and Learning on Reading Comprehension - Toni Indrayadi; Hengki Yandri; Dairabi Kamil (Universitas Jambi, Indonesia, 2020)
This study investigated the effect of contextual teaching and learning approach on students’ reading comprehension achievement. The quasi experimental design was employed in this study involving experimental and control groups. The experimental class received the contextual teaching and learning approach while the control class received the conventional approach. A multiple choice test was used as the research instrument to look at students’ reading comprehension. Data were analyzed through using the parametric levene statistic and non parametric tests. The result revealed that the experimental and control classes had significantly different reading comprehension achievement. It was proved by the mean score of reading comprehension achievement and mean score of gain of the experimental class was higher than the control class. This study also provided information for the researchers and lecturers about how to implement contextual teaching and learning in teaching reading.